The Effect of Financial Ratios on Profit Growth in Food and Beverage Companies Listed on the Indonesia Stock Exchange - Sarman Sarman; Idra Wahyuni; Masrullah, Masrullah (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this research is to collect data that shows how various financial ratios affect company profit growth. Some of the ratios used in the analysis are the Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Total Asset Turnover (TATO), and Profit Growth (Y). The study covers the period from 2021 to 2023 and is limited to food and beverage companies listed on the Indonesia Stock Exchange. Eighteen companies were sampled in this research. The t-test was used to test hypotheses, with classical assumption tests and multiple linear regression models employed for data analysis. The partial investigation shows that the Current Ratio (CR) does not significantly affect profit growth, while Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Total Asset Turnover (TATO) do have a significant impact. The Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Total Asset Turnover (TATO) are used as independent variables, while Profit Growth (Y) is the dependent variable in this study